Reviewing benefits and costs of hydropower development evidence from the Lower Mekong River Basin. (11th April 2019) - Intralawan, Apisom; Smajgl, Alex; McConnell, William; Ahlquist, Daniel B.; Ward, John; Kramer, Daniel B.
Abstract : In this paper, we examine the benefits and costs of hydropower development in the Mekong River Basin. We compare four major reports—the Mekong River Commission's (MRC's) Basin Development Plan Programme, Phase 2 (BDP2), the Strategic Environmental Assessment of Hydropower on the Mekong Mainstream (SEA), the Study on the Impacts of Mainstream Hydropower on the Mekong River (MDS), and the MRC's recent council study (CS)—in order to provide the basis for a comparative analysis of the major impact evaluation literature on mainstream dam construction in the Mekong River Basin for the period of 2010–2018. The primary objective of the review is to identify points of agreement, disagreement, inconsistency, and knowledge gaps. Both Mekong River Commission reports (BDP2 and CS) suggest extensive economic benefits for proposed hydropower development, whereas the SEA and MDS indicate that the net impact would be negative. The projected impacts of hydropower development on fisheries, sediment flows, and ecosystems vary widely both in economic and biophysical terms. However, all four reports point to decreased food security and loss of local livelihoods for millions of people as major concerns related to dam development. While considerable resources have been devoted to producing these important studies, the lack of standardization across reports, especially assumptions and methodologies for economic impacts, frustrates efforts at meaningful comparison of their findings and precludes the prospect of clear analytical outcomes or policy impacts. This article is categorized under: Engineering Water > Planning Water Human Water > Value of Water Engineering Water > Methods Abstract : Dams that are commissioned, under construction, or planned for the Mekong Basin.